Women’s sexual health in old age: identification of influencing factors using focus group interviews based on socioecological approach - Bagheri, Roghie; Momtaz, Yadollah Abolfathi; Foroughan, Mahshid; Shahboulaghi, Farahnaz Mohammadi (Springer, 2024)
Despite its importance and numerous benefits, sexual health in the elderly is often a neglected topic due to gender- and age-specific taboos and stereotypes, especially those addressing elderly women. A qualitative study was conducted using focus group interviews to explore the factors influencing the sexual health of elderly women. Twenty-four married elderly women from Tehran with different socioeconomic statuses and a mean age of 65.33 ± 5.32 participated in 7 focus group interviews. Content analysis was done following the deductive method of Elo and Kyngäs (2008) and based on the different levels of socioecological approach. Overall, the findings indicated the importance of influential factors at 5 different levels as the main categories which included 14 sub-categories. In addition to individual factors such as health and age-related changes, the participants regarded the role of sexual adaptation and the level of satisfaction with it in different periods of life as important factors contributing to the elderly women’s sexual health. The role of the husband’s health and the quality of the relationship with him along with the children influences were also found to have a decisive role at the interpersonal level. At higher levels, factors such as having privacy, the attitude of health care workers, and socio-cultural beliefs also contributed to sexual health. Results of this study are expected to provide the basis for future research and strengthen sexual health programs for the elderly based on social structures.